Beyond projetcts: The role of development partners in institutionalising renewable energy innovations. Lessons from the Global South - Joshua Philipp Elsässer; Harald Fuhr; Anna Fünfgeld; Markus Lederer; Jens Marquardt; Aparajita Banerjee; HyunAh Yi (German Institute of Development and Sustainability (IDOS), 2026)
Renewable energy has seen rapid uptake, particularly in the Global South. Solar energy projects have boomed in recent years, but uptake by countries is uneven. Beyond geophysical conditions, technological innovation, market dynamics and donor-driven "lighthouse projects", political institutionalisation has played a critical role in decarbonisation. In this policy brief, which is based on extensive research from Global South case studies, we argue that political institutionalisation is key to determining whether and how innovative solar initiatives become stabilised, scaled up, and mainstreamed. Drawing on the research project Institutionalizing Low Carbon Development in the Global South (INLOCADE) and expert contributions from a follow-up IDOS workshop, this policy brief synthesises comparative policy-relevant findings on how institutionalisation unfolds in various emerging economies of the Global South, including Brazil, Bangladesh, Cambodia, India, Indonesia and South Africa. Key messages: * Political institutionalisation - understood here as an enduring change of formal and informal rules and practices towards low-carbon development - is essential for making renewable energy projects sustainable by embedding them in conducive, stable governance frameworks. Isolated, donor-driven initiatives are at risk of provoking resistance and backlash, and of fading away once external support ends. * Multiple pathways for institutionalisation exist. State leadership, subnational action, alliances between development partners and communities, and crisis-driven coalitions can enable institutionalisation under different conditions. Policies should be tailored to the institutional realities of each context rather than using one-size-fits-all models. Similarly, development partners should assess local realities and adapt their strategies accordingly. * Distributive justice and participation must be actively supported. Political institutionalisation can lead to inequitable outcomes and reinforce exclusionary practices. Development partners should take a proactive role by aligning their interventions with inclusive and equitable approaches to ensure support for marginalised groups leads to socially just transitions, not just box-ticking. * Crises can be opportunities. Energy shortages and climate shocks can disrupt fossil-fuel lock-ins and open the door to innovation. Development partners need flexible instruments and strategies to help translate crisis-driven experiments into durable institutional change. * Development partners are catalytic, not deci-sive. They can accelerate change by providing finance, technical expertise, and legitimacy, especially when working with domestic actors beyond national governments. German and EU development cooperation should place greater emphasis on strengthening domestic institutional enviro-ments, including regulatory stability, administrative capacity, and actor coalitions that embed projects in lasting policy and organisational change. This helps ensure donor interventions contribute to sustained low-carbon transitions beyond initial project cycles.
Keywords: 320; Agenda 2030; energy; development financing and public finance; climate change; climate change mitigation; Global South